Effect of aloe vera on the proliferation phase of oral mucosal wound healing in rats - Primasari, Ameta; Yendriwati, Yendriwati; Minasari, Minasari; Buaya, Erlin Kristiani; Madani, Sri Ayu Winda; Sembiring, Kartika Nabila; Hidayati, Rizka (Faculty of Dentistry, Universitas Gadjah Mada, 2023)
Aloe vera is known as a medicinal plant containing an active substance acemannan thought to play a role in accelerating wound healing. This study aims to determine the effect of aloe vera extract on the proliferation phase of oral mucosa wound healing in rats by looking at epithelial thickening, epithelial gaps closure, growth of new blood vessels, and connective tissue growth. This research is a pure experimental study with a post-test only control group design. On the left buccal mucosa of the mouth of 24 white Wistar rats (n = 24), an incision was made by scalpel with 10 mm length and 2.5 mm depth. The rats were divided into 4 groups: groups 1 and 2 as controls, while groups 3 and 4 were applied with aloe vera extract made by maceration technique. Wound tissue was observed histologically with Hematoxylin-Eosin staining under a microscope with an image analyzer for measuring the thickness of epithelium. The analysis of epithelial gap width used morphometry, and the number of capillaries was counted manually. Connective tissue thickness was measured with Image-J software. These were carried out on days 7 and 14 after treatment and the data were analyzed with the independent t-test and Mann-Whitney test. The results showed that aloe vera extract had no significant effect on epithelial thickening on day 7 (p = 0.701) nor on day 14 (p = 0.639), but a significant effect was shown on epithelial gaps closing (p = 0.049), connective tissue thickening (p = 0.004), and capillary increase on day 7 (p = 0.049). It could be concluded that aloe vera extract could potentially accelerate the epithelial gaps closure, connective tissue thickening, and capillary increase during the proliferation phase of the oral mucosa wound healing.